2019
DOI: 10.3389/fcimb.2019.00234
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody AP3 Binds Galactomannan Antigens Displayed by the Pathogens Aspergillus flavus, A. fumigatus, and A. parasiticus

Abstract: Aspergillus fumigatus and A. flavus are the fungal pathogens responsible for most cases of invasive aspergillosis (IA). Early detection of the circulating antigen galactomannan (GM) in serum allows the prompt application of effective antifungal therapy, thus improving the survival rate of IA patients. However, the use of monoclonal antibodies (mAbs) for the diagnosis of IA is often associated with false positives due to cross-reaction with bacterial polysaccharides. More speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…2b) similar to data previously described [7][8][9][10] . These results indicate that the target epitope of MAb 4D1 is shared by various forms of the glycoprotein according to previously described findings 12 . The GNA binding studies demonstrated that the majority of carbohydrate components in TM CYA consisted predominantly of mannose residues.…”
Section: Immunoreactivity Patterns and Carbohydrate Components Of Thesupporting
confidence: 90%
“…2b) similar to data previously described [7][8][9][10] . These results indicate that the target epitope of MAb 4D1 is shared by various forms of the glycoprotein according to previously described findings 12 . The GNA binding studies demonstrated that the majority of carbohydrate components in TM CYA consisted predominantly of mannose residues.…”
Section: Immunoreactivity Patterns and Carbohydrate Components Of Thesupporting
confidence: 90%
“…Next, a novel tetrasaccharide construct consisting of β-1,2-mannopyranosyl trisaccharide and α-mannopyranoside was designed and suggested as a model of the C. albicans phosphodiester epitope (Dang et al, 2012). Glycoarrays formed by biotinylated oligosaccharides loaded on streptavidin-coated surfaces were previously shown to be indispensable instruments for the investigation of carbohydrate antigen recognition by immune cells (Komarova et al, 2015, 2018; Akhmatova et al, 2016; Paulovicova et al, 2016, 2017; Kurbatova et al, 2017; Argunov et al, 2019; Schubert et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Modern methods of carbohydrate chemistry permit efficient and stereospecific assembling of complex oligosaccharide chains representing different parts of polysaccharides of the fungal cell wall [ 22 , 23 , 24 ]. The arrays of oligosaccharides (glycoarrays) were shown to be indispensable tools in the assessment of ligand specificity of anti-carbohydrate monoclonal antibodies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ] and of antibodies in the blood sera [ 26 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%